2019
DOI: 10.21203/rs.2.15278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Δ133p53/FLp53 predicts poor clinical outcome in esophageal squamous cell carcinoma

Abstract: Background p53 isoform Δ133p53 is directly transactivated by p53 and antagonizes p53 activities in cancer progression. However, its correlation with prognosis and cancer recurrence in esophageal squamous cell carcinoma (ESCC) is still unclear.Methods Expression of Δ133p53 and Δ133p53/full-length p53 (FLp53) in tissues and serums of 180 ESCC patients was evaluated using qRT-PCR.Results Tissue Δ133p53 expression and Δ133p53/FLp53 ratio were significantly increased in ESCC tissue compared with adjacent normal tis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Accumulating evidence has shown that an increased ratio of ΔN-isoforms/p53α is associated with poorer overall survival or cancer aggressiveness, particularly for Δ133p53 in esophageal squamous cell carcinoma [62], Cholangiocarcinoma [63], and prostate cancer [64]. Here, we showed, that alternative p53isoforms, Δ133p53α and Δ160p53α, in particular, interfere with coexpressed p53α in DDT.…”
Section: Alternative P53-isoforms Show Loss-of-function In the P53-polι-dependent Ddt-pathway Mediating Homology-directed Bypass Of Replimentioning
confidence: 48%
“…Accumulating evidence has shown that an increased ratio of ΔN-isoforms/p53α is associated with poorer overall survival or cancer aggressiveness, particularly for Δ133p53 in esophageal squamous cell carcinoma [62], Cholangiocarcinoma [63], and prostate cancer [64]. Here, we showed, that alternative p53isoforms, Δ133p53α and Δ160p53α, in particular, interfere with coexpressed p53α in DDT.…”
Section: Alternative P53-isoforms Show Loss-of-function In the P53-polι-dependent Ddt-pathway Mediating Homology-directed Bypass Of Replimentioning
confidence: 48%